Genome Evolution in Bacteria Isolated from Million-Year-Old Subseafloor Sediment - William D. Orsi; Tobias Magritsch; Sergio Vargas; Ömer K. Coskun; Aurele Vuillemin; Sebastian Höhna; Gert Wörheide; Steven D’Hondt; B. Jesse Shapiro; Paul Carini (mBio, 2021)
ABSTRACT Beneath the seafloor, microbial life subsists in isolation from the surface world under persistent energy limitation. The nature and extent of genomic evolution in subseafloor microbes have been unknown. Here, we show that the genomes of Thalassospira bacterial populations cultured from million-year-old subseafloor sediments evolve in clonal populations by point mutation, with a relatively low rate of homologous recombination and elevated numbers of pseudogenes. Ratios of nonsynonymous to synonymous substitutions correlate with the accumulation of pseudogenes, consistent with a role for genetic drift in the subseafloor strains but not in type strains of Thalassospira isolated from the surface world. Consistent with this, pangenome analysis reveals that the subseafloor bacterial genomes have a significantly lower number of singleton genes than the type strains, indicating a reduction in recent gene acquisitions. Numerous insertion-deletion events and pseudogenes were present in a flagellar operon of the subseafloor bacteria, indicating that motility is nonessential in these million-year-old subseafloor sediments. This genomic evolution in subseafloor clonal populations coincided with a phenotypic difference: all subseafloor isolates have a lower rate of growth under laboratory conditions than the Thalassospira xiamenensis type strain. Our findings demonstrate that the long-term physical isolation of Thalassospira, in the absence of recombination, has resulted in clonal populations whereby reduced access to novel genetic material from neighbors has resulted in the fixation of new mutations that accumulate in genomes over millions of years. IMPORTANCE The nature and extent of genomic evolution in subseafloor microbial populations subsisting for millions of years below the seafloor are unknown. Subseafloor populations have ultralow metabolic rates that are hypothesized to restrict reproduction and, consequently, the spread of new traits. Our findings demonstrate that genomes of cultivated bacterial strains from the genus Thalassospira isolated from million-year-old abyssal sediment exhibit greatly reduced levels of homologous recombination, elevated numbers of pseudogenes, and genome-wide evidence of relaxed purifying selection. These substitutions and pseudogenes are fixed into the population, suggesting that the genome evolution of these bacteria has been dominated by genetic drift. Thus, reduced recombination, stemming from long-term physical isolation, resulted in small clonal populations of Thalassospira that have accumulated mutations in their genomes over millions of years.